1986
DOI: 10.1111/j.1365-3059.1986.tb02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting expression of resistance in pepper (Capsicum annuum) to blight caused by Phytophthora capsici in screening trials

Abstract: The effects of plant age, fungus isolate, zoospore concentration and inoculation method on the resistance of pepper (Capsicum annuum) to blight (Phytophthora capsici) were studied under controlled conditions. Each of the factors studied produced differing responses in the pepper lines tested hut line CNPH 286 proved to be a reliable source of resistance and is now being used in a breeding programme. An inoculation method for screening pepper lines for blight resistance is proposed, using a standardized zoospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
13

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 2 publications
3
34
0
13
Order By: Relevance
“…This result agrees with observations of Reifschneider et al (1986) and Echer (2001) about adult plant resistance to P. capsici. Phosphite enhanced resistance to P. capsici of Nathalie and Reinger hybrids up to equivalent CM 328 and 334 level.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This result agrees with observations of Reifschneider et al (1986) and Echer (2001) about adult plant resistance to P. capsici. Phosphite enhanced resistance to P. capsici of Nathalie and Reinger hybrids up to equivalent CM 328 and 334 level.…”
Section: Resultssupporting
confidence: 83%
“…Sweet and hot pepper resistance screening to P. capsici is highly dependent on plant age. Inoculation made at seedling stage may breakdown the resistance (Reifschneider et al, 1986;Echer, 2001). Adult plant resistance to Phytophthora is shown only after 60 days of age.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of P. capsici isolates differing in virulence will also dictate how resistant varieties should be deployed (Foster and Hausbeck 2010). Previous studies have reported differences in virulence and pathogenicity among P. capsici isolates on vegetable hosts (Kim and Hwang 1992;Oelke and Bosland 2003;Palloix et al 1988;Reifschneider et al 1986;Ristaino 1990). Isolate virulence responses vary by host.…”
Section: Introductionmentioning
confidence: 97%
“…x Phytophthora parasitica (Bowman & Graham, 1996); Capsicum annuun x Phytophthora capsici (Reifschneider et al, 1986); Passiflora edulis f. flavicarpa x Phytophthora nicotianae var. nicotianae (Cole et al, 1992), como sendo um dos fatores que afetam a expressão da resistência dos genótipos ao patógeno.…”
Section: Idade Das Plântulasunclassified